1986
DOI: 10.21273/jashs.111.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cytoplasmic and Vacuolar pH in Harvested Lettuce Tissue as Influenced by CO2

Abstract: ‘Climax’ lettuce (Lactuca sativa L.) exhibited more severe CO2 injury symptoms than ‘Salinas’ and ‘Winterhaven’ lettuce when exposed at 20°C to air for 1 day following treatment for 6 days at 0° with 15% CO2 in air. All 3 cultivars, however, had similar decreases as revealed by NMR analysis, of about 0.4 and 0.1 pH units in the cytoplasm and vacuole, respectively. This result indicates that variation in the buffering capacity was not related to differences in susceptibility to CO2 injury among these cultivars.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Factors other than assimilate levels associated with the time of day of harvest may also influence the sensitivity of lettuce to brown stain. Exposure of lettuce leaves to light after harvest was reported to decrease the incidence of brown stain (17). Light that lettuce receives prior to harvest in the afternoon may decrease the sensitivity of lettuce to C 0 2, but the mechanism by which light is exerting this influence is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Factors other than assimilate levels associated with the time of day of harvest may also influence the sensitivity of lettuce to brown stain. Exposure of lettuce leaves to light after harvest was reported to decrease the incidence of brown stain (17). Light that lettuce receives prior to harvest in the afternoon may decrease the sensitivity of lettuce to C 0 2, but the mechanism by which light is exerting this influence is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have consistently shown that higher levels of CO 2 have a significant impact on the physiological functioning of plants [4][5][6]. On the one hand, elevated CO 2 directly affects plant photosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Genera HCO 3 y H + (así como otros carbonatos) lo cual puede afectar al balance iónico, y por tanto, al pH intracelular (Wager, 1974b;Bown, 1985). Con estos cambios las funciones metabólicas normales no podrían ser sostenidas (Siriphanich y Kader, 1986). Smith (1963) indicó que el efecto del CO 2 sobre el contenido total de ácidos de las frutas no mostraba un panorama muy claro.…”
Section: Interacción De Altos Niveles De Co 2 Y Bajos Niveles De Ounclassified